Assessment of morbidity profile among workers of metallurgy factories processing aluminium in Howrah district of West Bengal - Debasish Biswas; Manabendra Sau; Gautam Paik; Kishore P. Madhwani; Amalendu Samanta (Journal of Family Medicine and Primary Care)
Introduction: Workers who work in metallurgy factories processing aluminium are at risk of exposure to various kinds of metals and chemicals. Objective: To describe sociodemographic characteristics and to find out morbidity profile of study participants . Methods: A cross-sectional O bservational descriptive study was conducted in two aluminium processing metallurgy factories in Howrah district of Indian state of West Bengal. The sample size for the proposed research study was 424 workers. Data were collected through a predesigned and pretested questionnaire and were subsequently analyzed by using suitable statistical package. Results: The mean age of the workers was 45.46 years with standard deviation of 10.25 years. Maximum (28.54%) respondents had completed primary standard, and majority of respondents were from upper middle class (34.67%). 16.75% of workers reported that they suffered from communicable disease s, and 76.42% of participants reported noncommunicable diseases. 63.44% of study participants were overweight. This study showed musculoskeletal discomfort in different joints and body parts in 23.35% of participants; 2.82% of participants had ventilatory defects of lung. 3.07% of participants were suffering from hearing loss, and 5.90% of participants had refractive error of eyes. Conclusions: Noncommunicable disease burden was higher than communicable diseases among study participants. Almost one out of four participants reported musculoskeletal discomfort in different joints and body parts.